Mobile application development - Peh, Ru Feng. (2013)
Today’s digital media environment is rapidly evolving, driven by the proliferation of devices powered by the best network coverage, broadband connections and Wi-Fi networks, there are increasing number of people watching the media content via the Internet, or from their personal media servers, whether at home, at the workplace and on the move.